Life reform and reform pedagogy in Hungary - Németh, András (Sodobna pedagogika, 2019)
Since the end of the 19th century, the modernisation processes of urbanisation and industrialisation taking place in Europe and the transatlantic regions have transformed the traditional societies, lifestyles and private lives of individuals and social groups. It is also characteristic of this period that social reform movements have appeared in large numbers - as a 'counterweight' to offset unprecedented, rapid and profound changes. Life reform is an umbrella term used to describe movements critical of modernisation whose main features have been the desire for a return to nature and naturalness, self-healing and the reclaiming of lost integrity. These movements were particularly active in the German and Austro-Hungarian monarchies after the end of the 19th century. New historical pedagogical research shows that a relatively close connection between the concepts of the major schools of reform pedagogy and life reform is discernible; furthermore, these close ties are evident in the educational reforms of the time. Thus, reform pedagogy is linked to life reform - and vice versa. Our work ties in with this stream of pedagogical research. To provide the necessary background, the first part of the study is a long-term project aimed at exploring relationships between life reform and reform pedagogy in the Austro-Hungarian monarchy and later in Hungary. In the second part of the study, we analyse connections between life reform and reform pedagogy after the FiSince the end of the 19th century, the modernisation processes of urbanisation and industrialisation taking place in Europe and the transatlantic regions have transformed the traditional societies, lifestyles and private lives of individuals and social groups. It is also characteristic of this period that social reform movements have appeared in large numbers - as a 'counterweight' to offset unprecedented, rapid and profound changes. Life reform is an umbrella term used to describe movements critical of modernisation whose main features have been the desire for a return to nature and naturalness, self-healing and the reclaiming of lost integrity. These movements were particularly active in the German and Austro-Hungarian monarchies after the end of the 19th century. New historical pedagogical research shows that a relatively close connection between the concepts of the major schools of reform pedagogy and life reform is discernible; furthermore, these close ties are evident in the educational reforms of the time. Thus, reform pedagogy is linked to life reform - and vice versa. Our work ties in with this stream of pedagogical research. To provide the necessary background, the first part of the study is a long-term project aimed at exploring relationships between life reform and reform pedagogy in the Austro-Hungarian monarchy and later in Hungary. In the second part of the study, we analyse connections between life reform and reform pedagogy after the First World War.rst World War.
Keywords: Austro-Hungarian monarchy; Avstro-Ogrska monarhija; gibanje za življenjsko reformo; independent Hungary; life reform; neodvisna Madžarska; pedagogika; pedagogy; reform pedagogy; reformska pedagogika